Digital Marketing and Consumer Behavior Models - Nila Prasetyaningsih; Anoesyirwan Moeins; Nandan Limakrisna (Greenation Research & Yayasan Global Resarch National, 2023)
Now covid19 vaccine has been tried out in those countries, when the vaccine is already being commercialized, how is the behavior of the Indonesian community in receiving the vaccine is that is communicated through social media, this is what is the goal in this research. Public service advertisements about COVID19 vaccines are available on various social media, one of which is on YouTube, with many versions. In this study took public service advertisements about the long version of the COVID19 vaccine. It is expected that public service advertisements can provide knowledge for users to know that COVID19 vaccines are important for children's immunity, and not contrary to any religion. This research uses the theory of Computer Mediated Communication. The paradigm used positivism with quantitative approaches, the nature of explanatory research and survey research methods. The population is to subscribe to 2146 public service advertisements as of March 2019 with a sample of 96 respondents taken using purposive sampling.